PEMBELAJARAN MAHARAH KALAM DENGAN STRATEGI ACTIVE KNOWLEDGE SHARING MENGGUNAKAN MEDIA REELS INSTAGRAM - Fadhiya Rahma Pratiwi; Jumhur Jumhur; Rendi Sabana (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study aims to explore the application of the Active Knowledge Sharing strategy combined with Instagram Reels as a digital media platform in teaching maharah kalam (Arabic speaking skills) among eighth-grade students at MTs Aisyiyah 1 Palembang. The study employs a mixed method approach, integrating both qualitative and quantitative data through classroom observation, interviews, and pre-test/post-test instruments. The implementation process revealed that students were actively engaged in learning activities, particularly in creating short video dialogues using Arabic expressions. The findings indicate a significant improvement in students' speaking abilities, supported by increased motivation, collaboration, and creativity during the learning process. The use of Instagram Reels effectively enhanced students' confidence and participation, making learning more enjoyable and relevant to their digital-oriented lifestyle. This study suggests that integrating familiar digital platforms with collaborative strategies can provide a meaningful impact on language learning outcomes. Furthermore, it highlights the importance of aligning instructional design with learners' media habits to create more engaging and contextualized experiences. The success of this approach also opens possibilities for applying similar strategies in other language skills or educational settings that aim to promote student-centered learning Keywords: Arabic Speaking, Digital Media, Instagram Reels